Short-Term Exercise Improves Not Only Muscle Strength But Also Lung Capacity, Endurance, and Quality of Life in Postmenopausal Vertebral Osteoporosis - Ülkü Uçar; Sibel Çubukçu Fırat; Tülay Ozdemir; Ersin Lüleci (Archives of Rheumatology, 2025)
Background/Aims: Investigate effects of short-term exercise on muscle strength, lung capacity, spinal mobility, endurance, and quality of life in postmenopausal osteoporosis without vertebral fractures. Materials and Methods: Forty-one postmenopausal osteoporosis patients (45–65 years) without fractures randomized to exercise (breathing, stretching, relaxation, balance, strengthening ×3 weekly for 8 weeks) vs control. Assessed back strength/endurance (Cybex Dynamometer, inclinometer), pulmonary function (spirometer), endurance (timed loaded standing), and QoL (QUALEFFO-41, SF-36). Results: EG showed significant improvements in back strength/endurance, pulmonary function (vital capacity, FVC, FEV₁, MMEF, MIP), and QoL (physical, mental, vitality subscales) (P < .05). Spinal mobility unchanged (P > .05). Conclusion: Short-term exercise significantly improves muscle strength, endurance, pulmonary function, and QoL in postmenopausal osteoporosis without fractures.